2021
DOI: 10.1080/14719037.2021.1916063
|View full text |Cite
|
Sign up to set email alerts
|

The many shapes and sizes of meta-governance. An empirical study of strategies applied by a well-advanced meta-governor: the case of Dutch central government in education

Abstract: This article aims at deepening the understanding of how central governments enact meta-governance. Drawing on meta-governance and policy network theory, a heuristic analytical framework of meta-governance strategies was applied on two contrasting Dutch education policy cases. The results show that the use of metagovernance strategies differs according to the degree of formal responsibility of the central government. Creating nodes in a policy network turns out to be a specific strategy, and the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Instead, the Foundation's power to influence governing norms and institutions is an indirect means of steering that involved filling monetary gaps that mobilized and galvanized other local governance actors and networks, a process sometimes referred to as “orchestration” (Abbott et al, 2016). Other environmental governance literatures on field‐building (Bartley, 2007; Phillips, 2018), agency (Betsill & Milkoreit, 2020), meta‐governance (Hooge et al, 2021), polycentricity (Carlisle & Gruby, 2019a) and environmental justice (Bennett, 2018; Bennett et al, 2021; Parsons et al, 2021) are ripe for engaging important questions of rights, sovereignty, and power in conservation philanthropy.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the Foundation's power to influence governing norms and institutions is an indirect means of steering that involved filling monetary gaps that mobilized and galvanized other local governance actors and networks, a process sometimes referred to as “orchestration” (Abbott et al, 2016). Other environmental governance literatures on field‐building (Bartley, 2007; Phillips, 2018), agency (Betsill & Milkoreit, 2020), meta‐governance (Hooge et al, 2021), polycentricity (Carlisle & Gruby, 2019a) and environmental justice (Bennett, 2018; Bennett et al, 2021; Parsons et al, 2021) are ripe for engaging important questions of rights, sovereignty, and power in conservation philanthropy.…”
Section: Discussionmentioning
confidence: 99%
“…In the school year 2015-16, all three policies mentioned before posed a demand on secondary schools. During that year, we conducted fieldwork in secondary schools as part of a larger research project studying how the central government enacts policies that touch on internal practices of relatively autonomous schools and how the latter respond to that (see also Hooge et al, 2021;Theisens et al, 2016;Waslander et al, 2018). To examine possible mechanisms to translate government policies into school practices, the aim of the original study was to select schools with a maximum of variety in school internal practices.…”
Section: Design Of the Study And Research Methodsmentioning
confidence: 99%
“…Specifically, as revealed in expert interviews, people were recommended by key policy actors through their alumni networks to sit on the boards of major nonprofit service operators so that they could act as the stewards of policies and service programmes. Similarly, in their study on the meta-governance of the Dutch central government in education, Hooge et al (2021) also found that promoting the interconnectedness and interdependency between network actors proved to be a salient network design strategy, and the Dutch government enacted this network design strategy by creating composite actors (partnerships or affiliations of network actors) that can be regarded as subnetworks within the policy networks.…”
Section: Substantive Uncertainty and Network Embeddednessmentioning
confidence: 98%
“…Klijn and Skelcher (2007) use the term 'governance network' to describe public policymaking and implementation through a web of relationships between government, business, and civil society actors. Many such networks operate rather 'in the shadow of hierarchy' (Damgaard and Torfing, 2011;Gjaltema et al, 2020;Hooge et al, 2021;Nederhand et al, 2019;Rhodes, 1996Rhodes, , 2007Whitehead, 2003).…”
Section: Introductionmentioning
confidence: 99%